Performance-based Durability Specifications of Fly Ash Concrete for Chloride-induced Environment - Jamil, Matarul (UNIMAS INSTITUTIONAL REPOSITORY, 2023)
Existing standard concrete practices under implementation of Standard Specifications for Building Works (SSBW) promptly altered from prescriptive specifications to Performance-based Durability Specifications (PBDS) as advocated by Eurocode 2. This study was carried out to overcome the chloride-induced attack problem on reinforced concrete (RC) structures settled under XS3 class exposure by utilising fly ash waste, producing non-destructive test (NDT) models and developing PBDS indicators model. The Taguchi Approach was used in this study with a combination of survey questionnaires, field investigation, experimental works and Statistical Product and Service Solutions (SPSS) modelling. The experimental work includes compressive strength (Cu), water absorption (WA), void of permeable voids (VPV) and ultrasonic pulse velocity (UPV) tests. Which, tested on tree different grades of ready-mix concretes, as well as concrete blended with Class-F fly ash with a 10% percentage increment up to 60%. Experimental work revealed that the Class-F fly ash was optimised at 30%. NDT models as represented by equation correlations of Cu1 = 31.699UPV1 – 84.641, Cu2 = 30.998UPV2 – 79.275 and Cu3 = 36.438UPV3 – 100.337. Developed PBDS indicators model equation was WA = 0.843VPV – 0.078UPV + 0.104. Meanwhile, "EXCELLENT" concrete quality rating bounded to Quality Rating Durability Compliance (QRDC) indicator values for UPV, VPV, WA and Cu should be more than 4.5 km/s, less than 10%, less than 7% and at least 55 MPa, respectively. The outcome indicators were found provide a flexible interface for client, designer or decision maker to make an accurate decision based on concrete performance, environmental sustainability and public user’s safety.